2018
DOI: 10.1111/ced.13412
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination during anti-tumour necrosis factor therapy for psoriasis

Abstract: Anti-tumour necrosis factor (anti-TNF) therapies have been associated with neurological complications, including in rare cases demyelinating disease. It is currently unknown whether patients who have received more than one immunosuppressive agent or anti-TNF have a greater risk of demyelination. We report the case of a 37-year-old woman with psoriasis who presented with an acute episode of demyelination while on anti-TNF therapy. This case was complicated by the fact that progressive multifocal leukoencephalop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…There were fourteen cases of worsening neurological disease despite cessation of anti-TNF therapy and several reports of new, clinically silent lesions detected on follow-up imaging. 202,[205][206][207][208][209][210][211][212][213][214][215][216] A case-control study in rheumatoid arthritis using a Canadian administrative claims and electronic medical records database showed a trend towards an increased rate of demyelination in 891 patients with no risk factors (for demyelination) with the authors suggesting that TNF antagonist therapy may increase risk of truly incident demyelinating events by ~30%, although failed to meet statistical significance (adjusted rate ratio 1.31 [95% CI 0.68-2.50]). 217 To date, trial and pharmacovigilance registry data have not shown any increased risk although this may relate to a low overall incidence, as well as exclusion of people at particular risk.…”
Section: Expert Consensusmentioning
confidence: 99%
“…There were fourteen cases of worsening neurological disease despite cessation of anti-TNF therapy and several reports of new, clinically silent lesions detected on follow-up imaging. 202,[205][206][207][208][209][210][211][212][213][214][215][216] A case-control study in rheumatoid arthritis using a Canadian administrative claims and electronic medical records database showed a trend towards an increased rate of demyelination in 891 patients with no risk factors (for demyelination) with the authors suggesting that TNF antagonist therapy may increase risk of truly incident demyelinating events by ~30%, although failed to meet statistical significance (adjusted rate ratio 1.31 [95% CI 0.68-2.50]). 217 To date, trial and pharmacovigilance registry data have not shown any increased risk although this may relate to a low overall incidence, as well as exclusion of people at particular risk.…”
Section: Expert Consensusmentioning
confidence: 99%
“…The case reports and case series that established this putative risk lacked comparator groups and cannot be used to establish the incidence or risk of disease. [3][4][5][6][7][8][9][10][11][12] Subsequent research has found mixed results. Two nested case-control studies identified elevated risks of TNF exposure among patients who developed neuroinflammatory diseases, 13,14 supporting the risk signal from case reports and case series.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-tumor necrosis factor alpha (TNFα) agents have been shown to significantly improve the quality of life in patients with several chronic immune-mediated inflammatory diseases [1]. However, an increased risk of multiple sclerosis (MS) or demyelinating events has been suspected after their use [2][3][4][5][6]. One of the first studies that postulated an association between anti-TNFα and MS pathogenesis was a randomized trial which was stopped early due to an increased rate of MS exacerbation among patients who received the drug lenercept [7].…”
Section: Introductionmentioning
confidence: 99%